Abstract semantics in the motor system? – An event-related fMRI study on passive reading of semantic word categories carrying abstract emotional and mental meaning. (March 2018) - Dreyer, Felix R.; Pulvermüller, Friedemann
Abstract: Previous research showed that modality-preferential sensorimotor areas are relevant for processing concrete words used to speak about actions. However, whether modality-preferential areas also play a role for abstract words is still under debate. Whereas recent functional magnetic resonance imaging (fMRI) studies suggest an involvement of motor cortex in processing the meaning of abstract emotion words as, for example, 'love', other non-emotional abstract words, in particular 'mental words', such as 'thought' or 'logic', are believed to engage 'amodal' semantic systems only. In the present event-related fMRI experiment, subjects passively read abstract emotional and mental nouns along with concrete action related words. Contrary to expectation, the results indicate a specific involvement of face motor areas in the processing of mental nouns, resembling that seen for face related action words. This result was confirmed when subject-specific regions of interest (ROIs) defined by motor localizers were used. We conclude that a role of motor systems in semantic processing is not restricted to concrete words but extends to at least some abstract mental symbols previously thought to be entirely 'disembodied' and divorced from semantically related sensorimotor processing. Implications for neurocognitive theories of semantics and clinical applications will be highlighted, paying specific attention to the role of brain activations as indexes of cognitive processes and their relationships to 'causal' studies addressing lesion and transcranial magnetic stimulation (TMS) effects. Possible implications for clinical practice, in particular speech language therapy, are discussed in closing.